Early Childhood Literacy and the Sense of Play (LEARNing Landscapes, 2009)
The author relates some of her experiences as a children’s book author/illustrator visiting schools, observing that in early childhood, creativity and sense of play are essential tools for teaching and learning. Believing that images and words play an equally important role in the learning process, she also includes a visual statement that early childhood literacy is empowering ...
Keywords: early childhoo; creativity; literacy; words; images; empowering; children's book